What's on your hard drive?. - O'Hanlon, Charlene (New York ACM, 2006)
Working with the same specific programs on a daily basis, developers often form intimate relationships with them. In fact, it's not rare to find programmers speaking of their tools in human terms, attributing bad habits to them and complaining about their mercurial behavior. Are you tired of your temperamental tools? Check out this month's WOYHD to find the ideal programs with which to spend the rest of your days of developing. And feel free to stop by http://www.acmqueue.com to share your love and hate relationships
Keywords: General literature